"Cut wires grating – single longitudinal wire" planar metastructure to achieve microwave magnetic resonance in a single wire - Kraftmakher, G.; Butylkin, V. (Advanced Electromagnetics, 2012)
Here we present metastructures containing cut-wire grating and a single longitudinal cut-wire orthogonal to grating’s wires. Experimental investigations at microwaves show these structures can provide strong magnetic resonant response of a single nonmagnetic cut-wire in dependence on configuration and sizes in the case when metastructures are oriented along the direction of wave propagation and cut-wires of grating are parallel to the electric field of a plane electromagnetic wave. It is suggested a concept of magnetic response based on antiparallel resonant currents excited by magnetic field of surface polaritons in many spatial LC-circuits created from cut-wire pairs of a grating and section of longitudinal cut-wire. Three separately observed resonant effects connected with grating, LC-circuits and with longitudinal cut-wire have been identified applying measurements in waveguides, cutoff waveguides and free space. To tune and mark resonance split cut-wires are loaded with varactor diodes.